Optimization and Molecular Characterization of Syngas Fermenting Anaerobic Mixed Microbial Consortium TERI SA1 - Singla, Ashish; Kumar, Sanjiv; Lavania, Meeta; chhipa, Hemraj; Kapardar, Rajkishor; Rastogi, Sachin; Lal, Banwari; Sarma, Priyangshu M (International Journal of Renewable Energy Development, 2017)
The present study focused on the optimization and molecular characterization of anaerobic mixed consortium TERI SA1 that can utilize synthesis gas as sole carbon source for volatile fatty acids production. Optimization study using Box- Behnken design and RSM methodology was carried out in order to investigate the effect of three medium factors on metabolite formation from synthesis gas bioconversion: (yeast extract (0.0–2.0 g/L), ammonium chloride (0.0–1.5 g/L) and corn steep liquor (0.0-10 g/L). Optimized parameters enhanced the production of volatile fatty acids upto 3.9 g/L, which indicated an increase of around 289 % from the non-optimized conditions. Furthermore, two approaches were used for isolation and phylogenetic identification of anaerobic consortium TERI SA1 involving 16S rRNA sequencing of culturable bacterial isolates as well as meta-genomic approach (by making a 16S rRNA gene library of total community DNA). Based on similarity search with NCBI database selected positive clones were most closely related with acetogenic microorganisms Clostridium scatalogenes, Clostridium carboxydivorans, Clostridium drakei and Uncultured Clostridium sp. and strains isolated by culturable method (ASH051 and ASH 052) with Clostridium scatalogenes, and Clostridium drakei. These strains have previously been reported for acetic acid production from syngas bioconversion.Article History: Received July 16th 2017; Received in revised form September 13rd 2017; Accepted Sept 28th 2017; Available onlineHow to Cite This Article: Singla, A., Kumar, S., Lavania, M., Chhipa, H., Kapardar, R., Rastogi, S., Lal, B., and Sarma, P.M. (2017) Optimization and Molecular Characterization of Syngas Fermenting Anaerobic Mixed Microbial Consortium TERI SA1.International Journal of Renewable Energy Development, 6(3), 241-251.https://doi.org/10.14710/ijred.6.3.241-251